The voice quality of sports coaches - Bučević, Anđela (Array, 2018)
The aim of this research paper was to examine the voice quality of sports coaches using the objective (acoustic) method. A total of 28 sports coaches (mean age 28.58, SD=5.08), from the City of Zagreb participated in this research. Recordings of the phonation of the vowel /a/ before and after one training session were obtained and analyzed using the PRAAT Program. Mean, minimal and maximal values of fundamental frequency, shimmer, jitter and harmonics-to-noise ratio were observed. The statistical analyses showed no statistically significant difference in acoustic voice quality of male and female coaches before and after the training session, or between male and female coaches. However, intra-individual differences among participants were observed, which may be significant in terms of their potential to affect the quality of their voices in the future.